Formation imprints in the kinematics of the Milky Way globular cluster system - Piatti, Andres Eduardo (2019)
We report results on the kinematics of Milky Way (MW) globular clusters (GCs) based on updated space velocities for nearly the entire GC population. We found that a 3D space with the semimajor axis, the eccentricity, and the inclination of the orbit with respect to the MW plane as its axes, is helpful in order to dig into the formation of the GC system. We find that GCs formed in situ show a clear correlation between their eccentricities and their orbital inclination in the sense that clusters with large eccentricities also have large inclinations. These GCs also show a correlation between their distance to the MW center and their eccentricity. Accreted GCs do not exhibit a relationship between eccentricity and inclination, but span a wide variety of inclinations at eccentricities larger than ∼0.5. Finally, we computed the velocity anisotropy β of the GC system and found, for GCs formed in situ, that β decreases from ≈0.8 down to 0.3 from the outermost regions toward the MW center, but remains fairly constant (0.7-0.9) for accreted ones. These findings can be explained if GCs formed from gas that collapsed radially in the outskirts, with a preference for relatively high infall angles. As the material reached the rotating forming disk, it became more circular and moved with a lower inclination relative to the disk. Half of the GC population was accreted and deposited in orbits covering the entire range of energies from the outer halo to the bulge.